Bioprospecting of Ureolytic Bacteria From Laguna Salada for Biomineralization Applications - Arias, Dayana; Cisternas, Luis A.; Miranda, Carol; Rivas, Mariella (Frontiers in Bioengineering and Biotechnology, 2019)
The processes of biomineralization, mediated by ureolythic bacteria, possess a wide range of technological applications, such as the formation of biocements and remediation of water and soil environments. For this reason, the bioprospecting of new ureolithic bacteria is interesting for its application to these technologies, particularly for water treatment. This study demonstrates the isolation, selection, and identification of halotolerant ureolytic bacteria from Laguna Salada (inland from San Pedro de Atacama) and the evaluation of their ability to precipitate calcium carbonate crystals in freshwater in the presence of calcium ions, as well as the ability to induce the precipitation of crystals from different ions present in seawater. Twenty-four halotolerant ureolytic bacteria whose molecular identification gives between 99 and 100% identity with species of the genus Bacillus, Porphyrobacter, Pseudomonas, Salinivibrio, and Halomonas were isolated. When cultivated in freshwater, urea, and calcium chloride, all species are able to biomineralize calcium carbonate in different concentrations. In seawater, the strains that biomineralize the highest concentration of calcium carbonate correspond to Bacillus subtilis and Halomonas sp. SEM–EDX and XRD analyses determined that both bacteria induce the formation of 9–33% halite (NaCl), 31–66% monohydrocalcite (CaCO¬3 × H2O), and 24–27% struvite (MgNH4PO4  6H2O). Additionally, B. subtilis induces the formation of 7% anhydrite (CaSO4). In seawater, B. subtilis and Halomonas sp. were able to precipitate both calcium (96 to 97%) and magnesium (63–67%) ions over 14 days of testing. Ion removal assays with B. subtilis immobilized in beads indicate a direct relationship between the urea concentration and a greater removal of ions. with similar rates to free cells. These results demonstrate that the biomineralization mediated by bacterial urea hydrolysis is feasible in both freshwater and seawater, and we propose its application as a new technology in improving water quality for industrial uses.